THE USE OF ELECTRONIC FLASHCARDS: ENHANCING VOCABULARY MASTERY THROUGH CLASSROOM ACTION RESEARCH - Hasanah, Uswatun; Anita, Anita; Oktaviana , Fadila; Fitriani , Dini (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
Vocabulary mastery is a critical component of language learning, yet many students struggle with acquiring and retaining new words effectively. This study examines the use of electronic flashcards as a tool to enhance vocabulary mastery through classroom action research in a secondary-level English classroom, following a cyclical process of planning, implementation, observation, and reflection, with data collected through tests, observations, and student feedback to evaluate their effectiveness. The findings indicate that electronic flashcards significantly enhance students’ vocabulary retention, recall, and motivation compared to traditional methods, with multimedia elements and interactive features contributing to an engaging learning environment. This study underscores the potential of technology-based tools in addressing challenges in vocabulary learning and highlights the importance of adopting innovative strategies to foster dynamic and effective teaching practices in language education. Thirty-two IX-G students at SMPN 5 Serang City participated in this research. Classroom action research was carried out in two cycles. Pre-test and post-test, questionnaires, along with interviews were used to collect data. The findings show that students succeeded in passing classical completeness by 62.5% in the pre-test, 78.1% in the post-test cycle 1, and 93.75% in the post-test cycle 2. Using electronic flashcards makes student easier to remember vocabulary, add new words, understand definitions and synonyms. It can be concluded that the use of electronic flash cards can help students become more proficient in vocabulary.